Standardization of Antimicrobial Sensitivity testing in Clinical Microbiology Laboratory: Bangladesh Perspective - Ahmed, Iftikhar (Bangladesh Journal of Infectious Diseases, 2019)
Abstract not available Bangladesh Journal of Infectious Diseases, December 2018;5(2):39-40